Energy and exergy analysis of a combined injection engine using gasoline port injection coupled with gasoline or hydrogen direct injection under lean-burn conditions. (11th February 2021) - Yu, Xiumin; Li, Decheng; Sun, Ping; Li, Guanting; Yang, Song; Yao, Chuanzhao
Abstract: Hydrogen is considered to be a suitable supplementary fuel for Spark Ignition (SI) engines. The energy and exergy analysis of engines is important to provide theoretical fundaments for the improvement of energy and exergy efficiency. However, few studies on the energy and exergy balance of the engine working under Hydrogen Direct Injection (HDI) plus Gasoline Port Injection (GPI) mode under lean-burn conditions are reported. In this paper, the effects of two different modes on the energy and exergy balance of a SI engine working under lean-burn conditions are presented. Two different modes (GPI + GDI and GPI + HDI), five gasoline and hydrogen direct injection fractions (0, 5%, 10%, 15%, 20%), and five excess air ratios (1, 1.1, 1.2, 1.3, 1.4) are studied. The results show that the cooling water takes the 39.40% of the fuel energy on average under GPI + GDI mode under lean-burn conditions, and the value is 40.70% for GPI + HDI mode. The exergy destruction occupies the 56.12% of the fuel exergy on average under GPI + GDI mode under lean-burn conditions, and the value is 54.89% for GPI + HDI mode. The brake thermal efficiency and exergy efficiency of the engine can be improved by 0.29% and 0.31% at the excess air ratio of 1.1 under GPI + GDI mode on average, and the average values are 0.56% and 0.71% for GPI + HDI mode. Highlights: The brake thermal efficiency and exergy efficiency are highest at λ of 1.1. The cooling water takes most of the heat but its exergy is the lowest. With hydrogen addition, the exergy destruction decreases obviously. HDI improves the brake thermal energy efficiency and exergy efficiency. Hydrogen engines have potentials to be more efficient by exhaust energy recovery.